Total phenolic and flavonoid contents and free radical scavenging components of Ficus nota Merr. (Moraceae) ethanolic leaf extract - Guerrero, R. P. (2019)
The leaves of Ficus nota or “tibig” are traditionally consumed as vegetable or used as herbal remedy. The primary aim of this research was to further evaluate the antioxidant and prooxidant nature of the plant by subjecting the ethanolic leaf extract containing alkaloids, flavonoids, phenols, terpenoids, saponins, and tannins to various general and specific antioxidant assays. Total phenolic and flavonoid content were found to be 348.3 ± 3.2 mg GAE/g and 2.64 ± 0.06 mg QE/g. The extract exhibited a concentration dependent inhibitory effect on DPPH, ABTS, and nitric oxide radical with an EC50 of 970.6, 269.8, and >5000 ppm respectively. Stimulation of superoxide, hydrogen peroxide, and hydroxyl radicals with median concentrations above 785.2 ppm was observed. The extract also showed a high dose dependent reducing capacity (EC50= 548.3 ppm) and metal chelating potential (EC50=27.53 ppm) towards iron. Results revealed that the plant extract possess both antioxidant and prooxidant properties depending on the concentration by which they are used. The dual nature exhibited by F. nota is deemed beneficial for the treatment and prevention of cardiovascular disease, diabetes, cancer, and aging. It can also aid in the maintenance of cellular homeostasis, host defense mechanisms, and various signaling processes in the body.